2019
DOI: 10.2134/agronj2018.11.0711
|View full text |Cite
|
Sign up to set email alerts
|

Planting Green Effects on Corn and Soybean Production

Abstract: No‐till farmers who want more from their cover crops (CCs) are delaying CC termination until the main crop is planted. Delaying termination can help dry wet soils and reduce erosion. This process is referred to as planting green (PG). We hypothesized that PG would (i) dry soil at main crop planting, but conserve soil moisture later in the growing season; (ii) reduce soil temperature; (iii) reduce slug damage on main crops; and (iv) not reduce main crop yield. This experiment was conducted in Pennsylvania betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(80 citation statements)
references
References 88 publications
3
75
2
Order By: Relevance
“…For instance, late‐terminated CCs or growing CCs for extended periods produce more biomass and exert greater changes in soil temperature compared with early‐terminated CCs with low biomass production. Reed, Karsten, Curran, Tooker, and Duiker (2019) found that soils under CCs terminated 1–3 wk before main crop (corn or soybean) planting were 0.7–2.4 °C warmer compared with soils under CCs terminated about 5 d after main crop planting due to more biomass produced under late CC termination. Also, CC impact on soil temperature can be greater earlier in the main crop growing season than later because CC residues decompose with time.…”
Section: Potential Factors Influencing Cover Crop Impactsmentioning
confidence: 99%
“…For instance, late‐terminated CCs or growing CCs for extended periods produce more biomass and exert greater changes in soil temperature compared with early‐terminated CCs with low biomass production. Reed, Karsten, Curran, Tooker, and Duiker (2019) found that soils under CCs terminated 1–3 wk before main crop (corn or soybean) planting were 0.7–2.4 °C warmer compared with soils under CCs terminated about 5 d after main crop planting due to more biomass produced under late CC termination. Also, CC impact on soil temperature can be greater earlier in the main crop growing season than later because CC residues decompose with time.…”
Section: Potential Factors Influencing Cover Crop Impactsmentioning
confidence: 99%
“…Therefore, planting winter cereal cover crops has been encouraged to effectively reduce nitrate-N in the tile drainage. Planting a winter cereal cover crop before corn could decrease corn yield as a result of reduced N availability in spring due to N immobilization caused by high C:N ratio of cover crop residue [12,13] or soil moisture depletion by the winter cereal early in the spring [14]. There have been studies on cover crop N release potentially happening simultaneously with cash crop N demand, but results have shown a decrease in cash crop N uptake [15][16][17].…”
Section: Of 10mentioning
confidence: 99%
“…Dicot weed species were more affected by BX compounds from winter cereals than were monocots (La Hovary et al., 2016), but whether this is true for row crops is not clear. In fact, soybean growth and yields were less affected by preceding cereal rye than corn in several studies; however, allelopathic activity was not measured so it is not clear if allelopathy contributed to these effects (Pantoja et al., 2015; Reed et al., 2019). Brassicas’ potential for allelopathic weed control was demonstrated in a recent review (Rehman et al., 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Another option may be to plant the row crop into the living CC and terminate it once the row crop emerges, past its sensitive period of germination. While planting green (planting into a living CC) is becoming more common, reduced corn populations and yields were reported in a Pennsylvania study where cereal rye was terminated within 5 d of corn planting (Reed et al., 2019). More research on this planting method is necessary to investigate how it affects germination and early growth of the row crop.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation